Correlative analysis of dissociative disorder among Kashmiri population - Nizam Ud Din Dar; Abdul Majid Gania; Tajamul Hussain Dhar; Aijaz Mohi Ud Din Bhat (Asian Journal of Medical Sciences, 2024)
Background: Dissociation is a complex psychopathology. Symptoms of dissociation are seen in different mental disorders. It is defined as a loss of integration between memory, identity, emotion, perception, behavior, and sense of self. Aims and Objectives: The aim of the study was to study sociodemographic variables of dissociative patients and to study psychiatric morbidities and their correlates concerning dissociative semeiology. Materials and Methods: This study was conducted from June to September 2023, where 51 persons were enrolled, who visited our patient department. Ethical clearance and consent were taken for the study. All the patients were diagnosed by a consultant psychiatrist according to the International Classification of Diseases-10 criteria. Sociodemographic profile pro forma, BG Prasad scale, and Dissociation Experience Scale-II were administered. Result: The majority of patients were from the 19 to 23-year-old age group, unmarried females residing in rural areas living in nuclear families having middle economic status who achieved middle education. The majority of patients had psychogenic non-epileptic seizures as a dominant symptom with school-related issues as a precipitant factor with the majority having a major depressive disorder. The correlation was significant at the 0.005 level. A correlation of P<0.005 for anxiety, depression, obsessive-compulsive disorder, and adjustment disorder with dissociative symptoms was seen. A P<0.005 was seen for sex, education, economic status, and occupation to that of dissociative symptoms. Conclusion: Dissociation symptoms have multiple comorbid psychiatric disorders comorbidly present. Precipitating factors need to be taken care of. Intervention should be multipronged. Psychological interventions may help manage different subconscious conflicts.